Political Connections, Corporate Governance and Audit Fees in Malaysia - Abdul Wahab, Effiezal Aswadi; Zain, M.; James, K. (Emerald Group Publishing Ltd., 2011)
Purpose – The purpose of this paper is to examine the relationship between political connection,corporate governance and audit fees in Malaysia. Specifically, it is argued that politically connectedfirms are perceived to be riskier and thus require auditors to undertake greater audit efforts which inturn lead to higher audit fee. Furthermore, it is also hypothesised that the demand for better corporategovernance practices requires more audit effort exert from the auditors, and the demand for higherquality work is expected to be stronger for politically connected firms as these firms are beingperceived to have higher risks. This is turn results in higher fees paid to the external auditor.Design/methodology/approach – This paper employs panel regression analysis. The panel data setconsists of 382 non-financial firms (1,022 observations) for three years from year 2001 to 2003.Findings – Based on 1,022 firm-year observations for the period of 2001 to 2003, the results reveal thatpolitically connected firms pay higher audit fees, while firms with better governance demand a higheraudit quality, leading to higher audit fees. However, there is no evidence to support that corporategovernance demands for a higher quality audit especially for politically connected firms.Originality/value – This paper contributes to the corporate governance-audit fees literature byexamining a large number of corporate governance variables based on the Malaysian Code on CorporateGovernance. In particular, instead of using several individual governance variables such as auditcommittee, board structure or composition, this study condensed the large number of corporategovernance variables into a single index. Furthermore, this study was conducted in Malaysia, which is aunique environment that offers clear identifiable segments based along ethnic line, whereby, politicallyfavoured firms are generally given special privileges by the government.